2016
DOI: 10.1016/j.ijcha.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrocardiographic findings and Cardiac Magnetic Resonance phenotypes in patients with Hypertrophic Cardiomyopathy

Abstract: BackgroundQ waves and negative T waves are common electrocardiographic (ECG) abnormalities in patients with Hypertrophic Cardiomyopathy (HCM). Several studies correlated ECG findings with presence and extent of fibrosis and hypertrophy; however, their significance remains incompletely clarified. Our study aimed to explain the mechanism behind Q and negative T waves by comparing their positions on a 12-lead ECG with phenotypes observed at Late Gadolinium Enhancement (LGE) Cardiac Magnetic Resonance (CMR).Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Parallel with our study, previous studies have also demonstrated that myocardial fibrosis detected as late gadolinium enhancement (LGE) in MRI correlates with fragmented QRS complex, ECG strain and T wave inversions 21–25. The association between LGE and pathological Q waves in hypertrophic cardiomyopathy patients has not been as congruent in previous studies 25 26. However, LGE can detect only regional fibrosis patterns, and ECG characteristics of diffuse fibrosis are less well studied.…”
Section: Discussionsupporting
confidence: 54%
“…Parallel with our study, previous studies have also demonstrated that myocardial fibrosis detected as late gadolinium enhancement (LGE) in MRI correlates with fragmented QRS complex, ECG strain and T wave inversions 21–25. The association between LGE and pathological Q waves in hypertrophic cardiomyopathy patients has not been as congruent in previous studies 25 26. However, LGE can detect only regional fibrosis patterns, and ECG characteristics of diffuse fibrosis are less well studied.…”
Section: Discussionsupporting
confidence: 54%
“…18 Furthermore, it was suggested that regional negative T waves correlate with regional scarring demonstrated by late gadolinium enhancement on cardiac MRI. 19 This would suggest that presence of scarring in the lateral wall is less present in genotype positive HCM.…”
Section: Discussionmentioning
confidence: 99%
“…4). Fibrosis 39 , diabetes 40 , or hypertrophy 41 are main risk factors potentially affecting cell coupling and consequently decreasing myocardial conduction, albeit with unclear ECG signature 42 . In our simulations, slow conduction promoted reentry in acute regional ischemia.…”
Section: Discussionmentioning
confidence: 99%